Hairy root transformation of Brassica rapa with bacterial halogenase genes and regeneration to adult plants to modify production of indolic compounds - Neumann, Madeleine; Prahl, Swantje; Caputi, Lorenzo; Hill, Lionel; Kular, Baldeep; Walter, Antje; Patallo, Eugenio P.; Milbredt, Daniela; Aires, Alfredo; Schöpe, Maria; O'Connor, Sarah; van Pée, Karl-Heinz; et al. (Phytochemistry (Oxford), 2020)
During the last years halogenated compounds have drawn a lot of attention. Metabolites with one or more halogen atoms are often more active than their non-halogenated derivatives like indole-3-acetic acid (IAA) and 4-Cl-IAA. Within this work, bacterial flavin-dependent tryptophan halogenase genes were inserted into Brassica rapa ssp. pekinensis (Chinese cabbage) with the aim to produce novel halogenated indole compounds. It was investigated which tryptophan-derived indole metabolites, such as indole glucosinolates or potential degradation products can be synthesized by the transgenic root cultures. In vivo and in vitro activity of halogenases heterologously produced was shown and the production of chlorinated tryptophan in transgenic root lines was confirmed. Furthermore, chlorinated indole-3-acetonitrile (Cl-IAN) was detected. Other tryptophan-derived indole metabolites, such as IAA or indole glucosinolates were not found in the transgenic roots in a chlorinated form. The influence of altered growth conditions on the amount of produced chlorinated compounds was evaluated. We found an increase in Cl-IAN production at low temperatures (8 °C), but otherwise no significant changes were observed. Furthermore, we were able to regenerate the wild type and transgenic root cultures to adult plants, of which the latter still produced chlorinated metabolites. Therefore, we conclude that the genetic information had been stably integrated. The transgenic plants showed a slightly altered phenotype compared to plants grown from seeds since they also still expressed the rol genes. By this approach we were able to generate various stably transformed plant materials from which it was possible to isolate chlorinated tryptophan and Cl-IAN. Brassica rapa has been transformed into transgenic root cultures harboring three different tryptophan-dependent halogenases from bacterial origin. These were regenerated to plants that stably contained the halogenase genes. Tryptophan was converted to Cl-tryptophan in planta and to other chlorinated indole derivatives by the plant enzymes. [Display omitted] •Hairy roots of Chinese cabbage were stably transformed with bacterial halogenase genes.•Halogenated tryptophan and compounds derived from the amino acid were found.•Production of halogenated compounds was induced by cold treatment.•Transgenic root cultures were regenerated to adult plants that stably contained the halogenase genes.•Regenerated plants produced the same set of halogenated metabolites as their progenitor.